Annual Plant Reviews Volume 43 2011
DOI: 10.1002/9781444339956.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Arabidopsis Thaliana

Abstract: Since the publication of the complete genome sequence of the model plant Arabidopsis thaliana, the precision annotation of the exact function of each gene has become a major research activity. Metabolomic analysis has much to offer in this endeavour and the small physical size and generation time of Arabidopsis make it a particularly attractive system for large-scale metabolomic data collection and analysis. In this review, we summarize the known phytochemistry of Arabidopsis, with particular emphasis on recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…For more detailed information the reader is referred to seminal volumes such as: Saito et al (2006), Weckwerth (2007) and Hardy and Hall (2011). Compact summaries have also been provided by Browne et al (2011) and Beale and Sussman (2011).…”
Section: The Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For more detailed information the reader is referred to seminal volumes such as: Saito et al (2006), Weckwerth (2007) and Hardy and Hall (2011). Compact summaries have also been provided by Browne et al (2011) and Beale and Sussman (2011).…”
Section: The Technologiesmentioning
confidence: 99%
“…The significant short life cycle and genetic advantages of this compact species have transformed a common weed into the most studied plant species on the planet. Inevitably, Arabidopsis has also rapidly become a favoured target for metabolomics studies (Beale & Sussman, 2011). Much functional genomics research has also been extended to include metabolic fingerprinting and profiling in the quest to understand better the function and molecular impact of specific gene mutations on the molecular patterning of plants.…”
Section: Metabolomics and Fundamental Plant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring such differences can greatly assist in determining the causal factors of natural variation in traits (Keurentjes, 2009). Linking metabolic profiles to phenotypic traits has only been reported by a small number of studies (as discussed by de Vos et al (2011) Beale et al (2011) Stewart et al (2011) and functional or regulatory analyses of metabolites are even rarer. Yet, these pioneering studies have shown that metabolism is strongly interlinked with complex genetic traits and may hold the key for their regulatory dissection.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%
“…Hence, the development of robust protocols for sample handling and data collection are essential components of any mQTL screen, where many hundreds of samples are involved. Willow (and other tree species) present a range of problems to large-scale screening and metabolomics data collection, which has been established on more tractable species such as Arabidopsis [ 21 , 22 , 23 ], with other significant studies on Solanaceae [ 24 , 25 ], cereals [ 26 , 27 ] and Medicago [ 28 ]. Metabolite screening of perennial woody plants has been reported for loblolly pine (for milled stem tissue) [ 29 ], but generally the heterogeneity of tissue types and physical/chemical properties requires considerable re-thinking of the protocols developed for annual crops.…”
Section: Introductionmentioning
confidence: 99%